2021
DOI: 10.3389/fimmu.2021.702505
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Dysfunction in Primary Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is an autoimmune disease which primarily affects the exocrine glands, but can also affect other organs, including the nervous system. Many studies have reported evidence of autonomic nervous system (ANS) dysfunction in pSS which may contribute to a wide range of symptoms and functional burden. Symptoms of ANS dysfunction are common and widespread among patients with pSS and are associated with other features of the disease, particularly fatigue. Accumulating data on the inter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
2
22
0
2
Order By: Relevance
“…Hypothesis 5 posits a role for the autonomic nervous system in fatigue 17,51,52 , and supporting this we found multiple abnormalities in autonomic function. Resting heart rate was elevated, and heart rate variability reduced; this suggests a rebalancing of parasympathetic versus sympathetic drive in favour of the latter.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hypothesis 5 posits a role for the autonomic nervous system in fatigue 17,51,52 , and supporting this we found multiple abnormalities in autonomic function. Resting heart rate was elevated, and heart rate variability reduced; this suggests a rebalancing of parasympathetic versus sympathetic drive in favour of the latter.…”
Section: Discussionsupporting
confidence: 86%
“…Hypothesis 5. Autonomic dysregulation is often a predictor for fatigue in other chronic illnesses 17 , and treating dysautonomia has shown promising results in the improving the symptoms of fatigue 18 . Autonomic dysregulation could also contribute to pCF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The autonomic nervous system deserves to be mentioned since it plays a key role in the regulation of the cardiovascular system and its dysfunction is prevalent among pSS patients, with a great impact on the quality of life ( 95 ). It appears that dysautonomia is the result of impairment in both parasympathetic and sympathetic nervous system, resulting in reduced heart rate and blood pressure variability ( 95 ). Reduced heart rate variability (HRV) is an independent predictor of a cardiac event and associated with sudden cardiac death in the general population ( 96 ).…”
Section: Cardiovascular Involvement In Sjogren’s Syndromementioning
confidence: 99%
“…However, a recent study has reported that BR is not associated with dopamine synthesis capacity 23 Decreased BR and increased incomplete blinking in patients with PD may cause tear film hyperosmolality, accelerated tear evaporation, and corneal damage 15 , 24 , 25 . Tear secretion is regulated primarily by the parasympathetic nervous system 13 , and the tear secretory function is often suppressed by autonomic dysfunction in PD due to PD-associated neurodegeneration 13 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%